2016
DOI: 10.1371/journal.pone.0162410
|View full text |Cite
|
Sign up to set email alerts
|

Red Anthocyanins and Yellow Carotenoids Form the Color of Orange-Flower Gentian (Gentiana lutea L. var. aurantiaca)

Abstract: Flower color is an important characteristic that determines the commercial value of ornamental plants. Gentian flowers occur in a limited range of colors because this species is not widely cultivated as a cut flower. Gentiana lutea L. var. aurantiaca (abbr, aurantiaca) is characterized by its orange flowers, but the specific pigments responsible for this coloration are unknown. We therefore investigated the carotenoid and flavonoid composition of petals during flower development in the orange-flowered gentian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Flower color polymorphism is due to variation in floral pigments, particularly anthocyanins and a predominance of pink, purple and blue with white combinations has been described as the result of changes and single mutations in the anthocyanin pathway (Richards 1986). In our study, orange and red colors were lost after hybridization probably due to changes in the biosynthesis pathway of anthocyanins and/or carotenoids, which responsible for those colours in flowers (Berman et al 2016), confirming the high polymorphism previously observed in other species. Warren and Mackenzie (2001) have considered that flower color is also regulated by selection related to environmental heterogeneity and stress tolerance.…”
Section: Morphological Characterizationsupporting
confidence: 91%
“…Flower color polymorphism is due to variation in floral pigments, particularly anthocyanins and a predominance of pink, purple and blue with white combinations has been described as the result of changes and single mutations in the anthocyanin pathway (Richards 1986). In our study, orange and red colors were lost after hybridization probably due to changes in the biosynthesis pathway of anthocyanins and/or carotenoids, which responsible for those colours in flowers (Berman et al 2016), confirming the high polymorphism previously observed in other species. Warren and Mackenzie (2001) have considered that flower color is also regulated by selection related to environmental heterogeneity and stress tolerance.…”
Section: Morphological Characterizationsupporting
confidence: 91%
“…splendens with strong red to reddishorange flowers corroborate the known fact that anthocyanins are the main pigment giving red color, whereas carotenoids are the main pigment giving the yellow and orange colors (Zhu et al 2010). For example, Berman et al (2016) found that a combination of red anthocyanins and yellow carotenoids resulted in the orange color of cultivated Gentiana lutea L. var. aurantiaca.…”
Section: Discussionsupporting
confidence: 69%
“…Secondary metabolites are the products of plant adaptation to the environment during their evolution. Anthocyanins as a kind of secondary metabolite play a vital role in various processes of plant development, such as providing color to organs to attract pollinators, and of antioxidant activity to protect plants from injury by biotic and abiotic stress [1][2][3][4]. In addition, anthocyanidins are widely used in food, health care products, and drugs for their excellent antioxidant activity [5,6].…”
Section: Introductionmentioning
confidence: 99%